Earlier supplier involvement for on-line mass customization (ESI-MC) - Chen, Yu. (2008)
In this thesis, we analyze the necessities of ESI for on-line mass customization from three aspects: new business model requirement, broad consideration of supplier capability and process efficiency improvement.